The association between digital technology use and depression among older people in China: a moderated mediation model - Wu, Qinmei; He, Wei; Wang, Jinfu; Du, Litao; Xue, Xiangli; He, Qiang; Pan, Yang; Chen, Si; Zhang, Xianliang (Frontiers in Psychiatry, 2025)
Objective: To investigate the association among multidimensional (Digital engagement, DE; Digital devices, DD; and Digital purpose, DP) digital technology use and depression in older Chinese, considering social participation as a mediator and physical activity level (PAL) as a moderator. Methods: Data on 5,744 participants (aged≥60) were extracted from the China Health and Retirement Longitudinal Study 2020 dataset. Depression was assessed using the 10-item Center for Epidemiologic Studies Depression Scale. Logistic regression examined the association between digital technology use and depression. The PROCESS program’s Model 4 evaluated the mediating role of social participation, while Model 7 assessed the moderating role of PAL. Results: Digital technology use was negatively associated with depression (DE, OR= 0.722, 95%CI: 0.609, 0.858; DD, OR= 0.739, 95%CI: 0.634, 0.860; DP, OR= 0.916, 95%CI: 0.881, 0.952). Various dimensions of digital technology use exerted direct effects on depression scores of 85.87% (DE, OR= -0.638, 95%CI: -1.036, -0.240), 86.09% (DD, OR= -0.526, 95%CI: -0.844, -0.208), and 87.82% (DP, OR= -0.173, 95%CI: -0.259, -0.087), respectively, and social participation mediated 14.13%, 13.91%, 12.18%. PAL exerted a positive moderating effect on the first half path of mediation, especially with the vigorous PAL (DE, OR= 0.591, 95%CI: 0.230, 0.952; DD, OR= 0.515, 95%CI: 0.206, 0.824; DP, OR= 0.157, 95%CI: 0.075, 0.239). Conclusions: Multidimensional digital technology use showed an association with depression in older adults. Promoting social participation through digital technology use is associated with lower depressive symptom scores, and vigorous PAL further strengthens this association, leading to improved mental health.